ZONASI ANOMALI UNSUR GEOKIMIA DI WEDA, KABUPATEN HALMAHERA TENGAH, MALUKU UTARA BERDASARKAN DATA UNIVARIAT DAN MULTIVARIAT - Fadhly, Ahmad; Syafri, Ildrem; Abdurrokhim, . (Bulletin of Scientific Contribution, 2017)
ABSTRACTThe research area is located in the Weda Region, Central Halmahera Regency, is a path of metal mineralization which belongs to the Halmahera magmatic arc. The study area has a coverage area of 10 km x 15 km. The purpose of this study is to reveal the availability of major elements content (Cu, Pb, Zn, Co, Ni, Mn, Ag, Li, K, Fe, Cr and Au) on river deposits in the form of maps of the major elements content. Geochemical data collection is done on intermittent river. The identification of the metal content of the samples taken was done in the PSMBP geochemistry laboratory using the Atomotic Absorbtion Spectrometry Logametri (AAS) method. A total of 12 elements have been analyzed for the levels in the highest samples of stream sediment and treated to obtain anomaly zone. In this case SPSS 21.0 software is used for identification anomaly based on the correlation value between elements, then the research area there are two elemental associations that have kinship in accordance with univariate statistics, multivariate with factor analysis test. The two elemental association elements: 1) Ni-Co-Li-K-Cr. The formation of Factor 1 shows a strong relationship between Ni as well as the associations Co, Li, K and Cr associated with the regional geological conditions of the study area, which is occupied by rock dominance mafic rock and ultramafiic rock. 2) Cu-Zn-Mn-Ag-Fe. The formation of Factor 2 was obtained based on the incorporation of geochemical data analysis results reflected from elemental associations in the surface environment of the Sulfide Ore Complex. The existence of this mineral is closely related to hydrothermal alteration. Keywords: Geochemistry, mineralization, Atomotic Absorbtion Spectrometry Logametri (AAS) method. ABSTRAKDaerah penelitian terletak di Daerah Weda, Kabupaten Halmahera Tengah, merupakan jalur mineralisasi logam yang termasuk ke dalam Halmahera magmatic arc, dan mempunyai cakupan wilayah 10 km x 15 km. Tujuan dari penelitian ini adalah untuk mengungkapkan keterdapatan kandungan unsur logam (Cu, Pb, Zn, Co, Ni, Mn, Ag, Li, K, Fe, Cr dan Au) pada endapan sungai dalam bentuk peta kandungan unsur logam tersebut. Pengambilan data geokimia dilakukan pada sungai intermitten. Identifikasi kandungan unsur logam dari contoh yang diambil dilakukan di laboratorium geokimia PSMBP menggunakan metoda Atomotic Absorbtion Spectrometri Logametri (AAS). Sebanyak 12 unsur telah dianalisis kadarnya di dalam percontohan sedimen sungai dengan kadar yang tertinggi dan diolah untuk mendapatkan zona anomalinya. Dalam hal ini software SPSS 21.0 dipakai untuk penentuan anomalinya berdasarkan nilai korelasi antar unsur, maka di daerah penelitian terdapat dua asosiasi unsur yang memiliki kekerabatan sesuai dengan data statistik univariat, multivariat dengan uji analisis faktor. Kedua asosiasi kekerabatan unsur tersebut adalah: 1) Ni- Co -Li-K-Cr, Pembentukan Faktor 1 memperlihatkan adanya hubungan yang kuat antara Ni serta asosiasi Co, Li, K dan Cr yang dikaitkan dengan kondisi geologi regional daerah penelitian, yaitu ditempati oleh dominasi batuan beku basa dan ultrabasa. 2) Cu-Zn-Mn-Ag-Fe. Pembentukan Faktor 2 didapat berdasarkan penggabungan hasil analisis data geokimia yang tercerminkan dari asosiasi unsur di lingkungan permukaan Komplek Bijih Sulfida. Keberadaan mineral ini erat kaitannya dengan alterasi hidrotermal. Kata Kunci: Geokimia, mineralisasi, metoda Atomotic Absorbtion Spectrometri Logametri (AAS).